Population Genetic Structure of Aphis gossypii Glover (Hemiptera: Aphididae) in Korea - Nam, Hwa Yeun (Insects, 2019)
Aphis gossypii Glover (Hemiptera: Aphididae) is a serious polyphagous agricultural pest worldwide. In the present study, we used eight microsatellite markers to investigate the genetic structure and diversity of A. gossypii populations in Korea. Samples were collected from 37 locations in Korea (18 populations in 2016, 14 populations in 2017, and five populations in 2018) from pepper plants. A. gossypii had low to moderate genetic diversity, and expected heterozygosity (H(E)) ranged from 0.354 to 0.719. A Mantel test of isolation by distance indicated no relationship between genetic structure and geographic distance among all populations (r(2) = 0.0004, p = 0.370), suggesting high gene flow among populations in Korea. Populations of A. gossypii in Korea were divided into two distinct genetic clusters (ΔK = 2). In 2016 and 2017, the genetic clusters changed into opposite genetic structures within one year mostly in northwest and southeast parts of Korea. Possible relevance of study results was discussed. Chemical control, cyclical parthenogenesis, and immigrants from the exterior might have resulted in this low genetic diversity and opposite genetic clusters.